The Glial Cells Respond to Spinal Cord Injury - Wang, Ruideng; Zhou, Rubing; Chen, Zhengyang; Gao, Shan; Zhou, Fang (Frontiers in Neurology, 2022)
It's been over 100 years since glial cells were discovered by Virchow. Since then, a great deal of research was carried out to specify these further roles and properties of glial cells in CNS. As it’s well known that glial cells including astrocytes, microglia, OLs and OPCs play an important role in supporting and enabling effective nervous system function in CNS. After SCI, these glial cells play different roles in spinal cord injury and repair. In this review, we will discuss in detail about the role of glial cells in the normal CNS and how they respond to SCI.